Autonomy and Unmanned Vehicles Augmented Reactive Mission and Motion Planning Architecture - MahmoudZadeh, Somaiyeh; Powers, David M.W.; Bairam Zadeh, Reza.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book addresses higher-lower level decision autonomy for autonomous vehicles, and discusses the addition of a novel architecture to cover both levels. The proposed framework's performance and stability are subsequently investigated by employing different meta-heuristic algorithms. The performance of the proposed architecture is shown to be largely independent of the algorithms employed; the use of diverse algorithms (subjected to the real-time performance of the algorithm) does not negatively affect the system's real-time performance. By analyzing the simulation results, the book demonstrates that the proposed model provides perfect mission timing and task management, while also guaranteeing secure deployment. Although mainly intended as a research work, the book's review chapters and the new approaches developed here are also suitable for use in courses for advanced undergraduate or graduate students.
Introduction to Autonomy and Applications -- State-of-the-art in UVs' Autonomous Mission Planning and Task Managing Approach -- State-of-the-art in UVs' Autonomous Motion Planning -- Advancing Autonomy by Developing a Mission Planning Architecture -- Mission Planning in Terms of Task-Time Management and Routing -- AUV Online Real-Time Motion Planning -- Augmented Reactive Mission Planning Architecture.
Keywords: Computational intelligence; Mathematical optimization; Artificial intelligence; Operations research; Control engineering; Robotics; Automation; Image processing -- Digital techniques; Computer vision; Computational Intelligence; Optimization; Artificial Intelligence; Operations Research and Decision Theory; Control, Robotics, Automation; Computer Imaging, Vision, Pattern Recognition and Graphics